Analisis Aplikasi Gf-Akuntansi Dalam Segi Keamanan Menggunakan Iso/Iec 17799 - Jajang Nurjaman; Hendro; Ilivia (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2019)
Security issues are one of the most important aspects of an application. Security issues often get less attention from application designers and managers. If it interferes with application performance, security issues are often ignored or even eliminated. PT Sukses Bintan Permata Kota Tanjungpinang is a company engaged in the field of work. distributor of food and staples. The purpose of this study is to determine the level of security in the GF-Accounting application, which is used by PT. The success of Bintan Permata, the city of Tanjungpinang.ISO / IEC 17799 published by the International Organization for Standardizations (ISO) and the International Electrotechnical Commission (IEC), is a code of practice to provide a framework as an information security standard. ISO / IEC 17799 as a method of this research, using the Security policy component, Physical and environmental security, Communications and Operations Management, and Access Control.The results of the study state that the security of the GF-Accounting application in each component is declared good, which can be seen on average from this GF-Accounting security analysis, all components average a value of 75.5% or a fair / good level criterion, such as Security Policy. has reached the highest value, namely 87%. then Physical and Environmental Security with a value of 72.5%, Communication and Operation management with a value of 75% and Access control with a value of 67%.